Effects of Short-Acting Beta-Agonist (SABA) Alone and SABA with Inhaled Corticosteroids in the Management of Asthma among Children - Muhammad Amir, Ghulam Shabir Laghari, Muhammad Siddique Rajput, Faeza Husnain, Farina Saqib, Dilawer Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: However, the comparative efficacy of SABA alone vs SABA in conjunction with ICS in the treatment of childhood asthma remains an important topic of research. Understanding the comparative efficacy of SABA alone versus SABA in conjunction with ICS in the treatment of childhood asthma is critical for evidence-based decision-making. Methodology: This randomized controlled study (RCT) included 80 children aged 6 to 12 years who were diagnosed with mild chronic asthma. The participants were separated into two groups: SABA alone and SABA plus ICS. For symptom alleviation, the SABA alone group got as-needed treatment with a short-acting beta-agonist (SABA). The SABA with ICS group got SABA therapy on a regular basis for symptom alleviation, as well as daily inhaled corticosteroid (ICS) therapy for maintenance. To compare the outcomes of the two groups, statistical analysis was done using an independent t-test. A statistically significant p-value of less than 0.05 was evaluated. Results: Spirometry measures were taken to quantify vital capacity (VC), forced expiratory volume at one second (FEV1), and the FEV1/VC ratio. Both groups had lower baseline values for these measures, indicating decreased lung function. However, both groups’ lung function improved significantly following the intervention (p<0.05). Practical Implication: The findings of this study can not only educate clinical practice, but also assist healthcare practitioners in making informed treatment decisions in order to enhance asthma management and outcomes for patients. Conclusion: According to the data, combining these drugs can enhance symptom management and lung function in children with moderate chronic asthma. Keywords: Asthma, Lung Function test, Forced expiratory volume, Short Acting Beta Agonist, Inhaled Corticosteroids, Children.